Pengaruh Sosialisasi Terhadap Peningkatan Pengetahuan Dan Sikap Tentang Gizi Kesehatan Reproduksi Pada Remaja Di Kecamatan Deleng Pokhkisen Kabupaten Aceh Tenggara - Halimatussakdiyah Lubis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the causes of the problem of adolescent nutritional status in Indonesia is a practice problem or action that is affected by a lack of nutritional knowledge. This study aims to analyze the effectiveness of counseling in increasing the knowledge and attitudes of pregnant women regarding nutrition and food safety. This research uses a quasi-experimental method. The design used is a group pre-test and post-test design. The population in this study were teenagers in Deleng Pokhkisen District, Southeast Aceh Regency. The sample was taken by purposive sampling of as many as 30 teenagers. The research was carried out from 5 October – 4 December 2023, spanning 12 days. analyzed statistically with a paired t-test. significance using α=0.05.